Pengaruh Pendidikan Kesehatan tentang Pemeriksaan Payudara Sendiri (SADARI) terhadap Tindakan SADARI di UPT Puskesmas Tembuku 1 Bangli - Ni Ketut Citrawati; Ni Luh Putu Thrisna Dewi (Jurnal Kesehatan Indonesia, 2022)
Breast cancer has highest prevalence in Indonesia which is 42,1 per 100,000 population of Indonesian women suffered breast cancer and the average of rate death is 17 per 100,000 population. Breast self-examination is an early detection or screening method to detect early breast tumors or lumps. The purpose of this study was to determine the effect of health education on self-breast examination (BSE) on conscious action. The method of this research was quantitative design of quasi-experimental pretest-posttest control group design, the determination of the sample of this study by purposive sampling of 40 women of childbearing age divided into 2 groups, 20 samples of treatment groups and 20 samples of control groups.The measurement of awareness action used a questionaire before intervention in the treatment and control groups, tabulation of conscious action data after intervention in the treatment and control groups, data analysis of conscious action before and after being given health education about awareness with the paired T Test if the data distribution is normal and if not distributed normal with the Wilcoxon sign test (f). The results showed that the p value in the treatment group is 0,000, while the p value in the control group is 0,102 which indicates that the p value in the treatment group and the control group is 0,000. There is a significant effect on the group that was given treatment than the control group. The results of this study are expected to consider increasing the socialization program on the implementation of breast examination held.